NATURAL STONE AND WORLD HERITAGE salamanca (spain). - Pereira, Dolores ([Place of publication not identified], CRC Press, 2019)
Heritage stones are those stones that have been used for many years, even centuries, to build the historic buildings and monuments of places around the world. Some of these stones are still being used for construction, but others are no longer used, either because quarries were exhausted or closed or because architects and constructors do not know about their particularities and importance. Several scientific papers discuss many of these stones, and a number of papers are currently being prepared, but this book is the first to emphasize the importance and significance of natural stone in the construction of a city, Salamanca, recognized as a World Heritage Site by UNESCO since 1988. In light of this recognition, Salamanca has a duty to preserve all historic buildings that make up the city by restoring those that are starting to deteriorate centuries after their construction. This book describes the buildings, the stones (all quarried centuries ago in the surrounding area), and the stone quarries, some of them inactive for many years, but that should still allow extraction of blocks on demand to restore and replace damaged specimens in the buildings, preserving the very character that saw the city receive recognition by UNESCO in the first place. There are many other places around the world that should follow this initiative and disseminate the importance of their heritage stones. This book will be of interest to professionals and academics in Geology, Engineering, architectural and artistic work in stone, both construction and conservation, but also to the general public.
OCLC-licensed vendor bibliographic record.
Keywords: Historic buildings -- Conservation and restoration -- Spain -- Salamanca; Building stones -- Spain -- Salamanca; Cultural property -- Spain -- Salamanca; TECHNOLOGY & ENGINEERING / Construction / General; SCIENCE / Earth Sciences / Geology; TECHNOLOGY / Construction / General